Sustainability analysis: case study agroproductive systems managed by afro-ecuadorians in the northern area of Ecuador - Lora Mosquera, Aide Verónica; Heredia Renjifo, Marco Gerardo; Cayambe Terán, Jhenny Marlene (SATHIRI, 2023)
In the northern zone provinces of Ecuador, Carchi, Imbabura, Esmeraldas and Sucumbíos, there are Afro-Ecuadorian ethnicity producers who are dedicated to agricultural production, with conventional agricultural large scale methods such as monoculture, an intensive use and mismanagement of supplies and pesticides, with poor agricultural practices, they cause the ecosystems deterioration and wastage and the environmental contamination, being necessary to determine the sustainability indices in the agro-productive systems to the establishment of measures aimed at the protection of ecosystems, looking to improve the productivity levels in their territory. This research aimed to determine the sustainability of Afro-Ecuadorian agro-productive systems in the northern zone; The information gathering was performed in field visits through surveys in the communities of Mira Canton, Carchi Province, in Ibarra Canton, Imbabura Province, in San Lorenzo Canton, Esmeraldas Province and in Lago Agrio Canton, Sucumbíos Province. Through the SAFA software using, a sustainability analysis determined in four dimensions was established: good governance, environmental integrity, economic resilience and social well-being, creating a sustainability polygon, showing a limited level of sustainability in all dimensions with an average of 11.72% in the North Zone, regarding to Carchi Province an average of 12.97% is established, followed by Esmeraldas with 12.28%, Imbabura with 11.32% and Sucumbíos with 10.33%. The sustainability levels determine that “these agro-productive systems are not sustainable enough in economic, social, environmental and governance aspects”; due to they show a limited average of 11.04%, requiring a specific intervention plan for each province where the governmental agencies and/or non-governmental organizations intervene in order to improve the sustainability of the agro-productive systems in the Afro-Ecuadorian communities of the northern area of the country.
Keywords: Sustainability; Afro-Ecuadorians; production systems; SAFA